Resumption in Italy (Quarterly Journal of Economics, 1887)
Journal Article Resumption in Italy Get access The Quarterly Journal of Economics, Volume 1, Issue 3, April 1887, Pages 356–357, https://doi.org/10.1093/qje/1.3.356-a Published: 01 April 1887